Referral Marketing and Corporate Trust Icon : Strategies to Increase Customer Loyalty through Customer Satisfaction - Ernita Eva Aviyanti; Chandra Kartika; Rudiatno (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this research is to determine the effect of referral marketing and corporate trust icons on radical customers through customer satisfaction at Mie Barracung. This study employs a descriptive research design with explanatory research methods. Sampling was conducted using purposive sampling as the sampling technique. The sample used in this study consists of 100 respondents who are customers of Mie Barracung Manukan Surabaya. This research utilizes a structural equation modeling (SEM) approach - SmartPLS 4.0.9.3, which includes the inner model process, outer model, and hypothesis testing (bootstrapping) to test the significance of the overall model and the predetermined paths. The findings indicate that referral marketing has a direct effect on customer satisfaction at Mie Barracung Manukan Surabaya..Trust icon corporate directly does not affect radical customers at Baraccung noodles Manukan Surabaya. Customer satisfaction directly affects radical customers at Baraccung noodles Manukan Surabaya. Referral marketing indirectly affects radical customers through customer satisfaction at Baraccung noodles Manukan Surabaya. Trust icon corporate indirectly does not affect radical customers through customer satisfaction at Baraccung noodles Manukan Surabaya.